Halide Perovskite Quantum Dots Photosensitized‐Amorphous Oxide Transistors for Multimodal Synapses. Issue 11 (16th September 2020) - Subramanian Periyal, Srilakshmi; Jagadeeswararao, Metikoti; Ng, Si En; John, Rohit Abraham; Mathews, Nripan
Abstract: Deployment of novel artificial synapses serves as the crucial unit for building neuromorphic hardware to drive data‐intensive applications. Emulation of complex neural behavior through conventional Si‐based devices requires a large number of elements which increases fabrication complexity and brings challenges of connectivity. Hence, there is a need to investigate alternative material systems and device architectures for emulating richer neural behavior comprising of lesser elements. Herein, a thin‐film transistor‐like synaptic device using all‐inorganic cesium lead bromide (CsPbBr3 ) perovskite quantum dots (QDs) and amorphous indium gallium zinc oxide semiconductor active material is explored for brain‐inspired computing. The incorporation of CsPbBr3 QDs as a photosensitizer aids in realizing light‐dependent synaptic memory. Furthermore, type II heterostructure can serve as a basis for electro‐optical programming. The proposed artificial synapse demonstrates a materials combination that can decouple optical absorption and charge transport property and provides freedom to tune the spectral region. Harnessing the advantages of novel materials, the devices obey spike‐timing‐dependent plasticity rules, inculcate associative learning and linear nonvolatile blind updates. This architecture paves way for efficient building of neuromorphic hardware elements with facile tunability and tailorable plasticity. Abstract : The incorporation of cesium lead bromide quantum dots as a photosensitizer aids in realizing light‐dependent synaptic memory of amorphous oxide based thin‐film transistors. Formation of type II heterostructure serves as a basis for optical writing/electrical erasing and displays nonvolatile electro‐optical memory. Inspired by biological visual perception, an artificial synapse adaptive to mimic functions associated with the visual cortex is demonstrated.